The business management of the village government in managing Village Owned Enterprise - Nikki Prafitri; Paulus Israwan Setyoko; Dyah Retna Puspita (Masyarakat, Kebudayaan dan Politik, 2018)
Local Government business management through a Village Owned Enterprise is a new public management application. The Village government’s business is carried out by applying business techniques, values and principles. The purpose of the Village Owned Enterprise is to increase the village’s original income and economy. The diﬀerences involved in the success of the Village-Owned Enterprise management is triggered by diﬀerences in the application of government business principles, consisting of several aspects including the business plan, capital, accountability, transparency, reporting, corporate accounting and the payroll system. This research focused on the application of government business principles in relation to the management of the Village Owned Enterprise. The research used a qualitative research method and interactive data analysis method. Furthermore, the research was conducted in two villages; Serang Village, Karangreja Subdistrict, Purbalingga Regency and Pernasidi Village, Cilongok Subdistrict, Banyumas Regency. The research findings showed that the involvement of the village head in the preparation and socialisation of the business plan, the delegation of authority in relation to capital, the commitment to implementing transparency, the control over the officer's accountability and reporting, audits on accounting and the participation and cooperation from various stakeholders to motivate the officers in managing Village-Owned Enterprise for village welfare. The listed are the preconditions of village government business management through the Village-Owned Enterprise. Based on the funding of the phenomenon in the field regarding village business management through the Village Owned Enterprise, there are several recommendations to strengthen the management of the economic institution itself.